2017
DOI: 10.7755/fb.115.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of leader material on catches of shallow pelagic longline fisheries in the southwest Indian Ocean

Abstract: Abstract-Catches from a commer cial longline fishery targeting sword fish (Xiphias gladius) on monofila ment nylon leaders were compared with catches on wire leaders in the Indian Ocean. More taxa were caught on wire leaders, which also showed higher catch rates (13% and 56%, in number and weight, re spectively) of blue shark (Prionace glauca). In contrast, catch rates of swordfish were not significantly af fected by leader material. Nylon leaders showed lower athaulback mortality for most bony fishes, ex cept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…For pelagic longline fisheries, restrictions can be implemented on mainline length, the use of wire leaders on gangions, the number, size, and type of hooks, and fishing depth. Our study confirmed the Cojímar fleet's use of wire near hooks on gangions, particularly in nocturnal sets, which increases the retention of sharks (Santos et al 2017). Changing longline leaders from wire to monofilament can allow some sharks to bite through and escape if captured (Shiffman and Hammerschlag 2016a), although several studies have compared wire leaders to monofilament leaders with conflicting results (Branstetter and Musick 1993;Ward et al 2008;Romanov et al 2010).…”
Section: Management Of Cuba's Small-scale Pelagic Longline Fisheriessupporting
confidence: 75%
“…For pelagic longline fisheries, restrictions can be implemented on mainline length, the use of wire leaders on gangions, the number, size, and type of hooks, and fishing depth. Our study confirmed the Cojímar fleet's use of wire near hooks on gangions, particularly in nocturnal sets, which increases the retention of sharks (Santos et al 2017). Changing longline leaders from wire to monofilament can allow some sharks to bite through and escape if captured (Shiffman and Hammerschlag 2016a), although several studies have compared wire leaders to monofilament leaders with conflicting results (Branstetter and Musick 1993;Ward et al 2008;Romanov et al 2010).…”
Section: Management Of Cuba's Small-scale Pelagic Longline Fisheriessupporting
confidence: 75%
“…In terms of interpretation of the models, the effects of the leader material seemed to be the most important factor for explaining the blue shark catch rates, followed by spatial effects, seasonality, and environmental variables. The higher catch rates found when wire leaders were used make sense from biological and fishery operational points of view, as wire leaders make bite‐offs of the sharks less likely to occur while hooked in the longlines (e.g., Afonso, Santiago, Hazin, & Hazin, ; Santos, Lino, & Coelho, ). The conclusions regarding the spatial and seasonal effects taken from this study also seem to be in line with what is common knowledge from the commercial fishermen that empirically mentions higher catches of sharks particularly in the second semester of the year and toward eastern longitudes, closer to mainland Africa.…”
Section: Discussionmentioning
confidence: 99%
“…An influence of fish species on mortality was reported for each gear type except purse seines (Broadhurst et al, 2008(Broadhurst et al, , 2009Davis, 2007;Digre et al, 2010;Falterman and Graves, 2002;Gisbert and López, 2008;Jurvelius et al, 2000;Morfin et al, 2017;Olla et al, 1997;Santos et al, 2017). Such differences are likely explained by differences between species in, for example, morphology and endurance.…”
Section: Influence Of Fish Characteristics On Mortalitymentioning
confidence: 97%
“…Esox Lucius Davis (2007) Coho salmon Oncorhynchus kisutch Northern rock sole Lepidopsetta polyxystra Pacific halibut Hippoglossus stenolepis Walleye pollock Theragra chalcogramma Pacific halibut Hippoglossus stenolepis Davis and Ottmar (2006) Northern rock sole Lepidopsetta polyxystra Pacific halibut Hippoglossus stenolepis Sablefish Anoplopoma fimbria Walleye pollock Theragra chalcogramma Davis and Schreck (2005) Pacific halibut Hippoglossus stenolepis Kerstetter and Graves (2006b) White marlin Tetrapturus albidus Kerstetter and Graves (2008) Sailfish Istiophorus platypterus Kestin et al (1991) Rainbow 2014Pink snapper Pagrus auratus Milliken et al (1999) Cod Gadus morhua Milliken et al (2009) Cod Gadus morhua Misund and Beltestad (1995) Herring Clupea harengas Misund and Beltestad (2000) Horse mackerel Trachurus trachurus Mackerel Scomber scombrus Saithe Pollachius virens Mitchell et al (2002) South American pilchard Sardinops sagax (Morfin et al 2017) European Olla et al (1997) Sablefish Anoplopoma fimbria Walleye pollock Theragra chalcogramma Olla et al (1998) Sablefish Anoplopoma fimbria Olsen et al (2012) Herring Clupea harengus Olsen et al (2013) Cod Gadus morhua Orsi et al (1993) Chinook salmon Oncorhynchus tshawytscha Pálsson Ó et al (2003) Cod Gadus morhua Pribyl et al (2011) Black Richards et al (1995) Pacific halibut Hippoglossus stenolepis Rudershausen et al (2008) Black sea bass Centropristis striata Rudershausen et al (2014) Black sea bass Centropristis striata (Santos et al 2017) Black Ocyurus chrysurus Stewart (2008) Snapper Pagrus auratus Suuronen et al (1996a) Herring Clupea harengus Suuronen et al (1996b) Cod Gadus morhua Suuronen et al (1996c) Herring Clupea harengus Suuronen et al (2005) Cod Gadus morhua Tenningen et al (2012) Herring Clupea harengus Turunen et al (1994) Brown trout Salmo ...…”
Section: Purse Seinesmentioning
confidence: 99%
See 1 more Smart Citation